Competence, Agile Leadership, Social Media Engagement, Reputation and Business Performance of MSMEs in Bekasi Regency - Handayani, Milda; Umar, Haryono; Tanuwijaya, Justine (Dinasti International Journal of Management Science, 2024)
This quantitative study aims to analyze the influence of Competence, Agile Leadership, Social Media Engagement, Reputation on Business Performance of MSMEs in Bekasi Regency. The research sample was 277 MSMEs, using Structural Equation Modeling (SEM) AMOS. The results show that competence has a positive effect on business performance, competence has a positive effect on reputation, agile leadership has a positive effect on reputation, but agile leadership does not affect business performance, social media engagement has a positive effect on business performance but social media engagement does not affect reputation. Reputation has a positive effect on business performance. Full mediation occurs when reputation mediates competence and business performance, the same thing happens when reputation mediates agile leadership and business performance, but when reputation mediates social media engagement and business performance, partial mediation occurs. The implications of the theory provide new developments and insights related to the theory of competence, agile leadership, social media engagement, reputation and business performance. In practice, MSMEs in Bekasi Regency can play a more active role in welcoming government programs for the development of competencies, expanding current insights, and utilizing social media to build business reputation as a supporter of improving business performance in the future so that they can compete in their respective zones.